UHI and temporal study of urban growth: a study of the Klang Valley area - Ibrahim, Illyani; Abu Samah, Azizan; Fauzi, Rosmadi (2014)
The growth in urbanization has received much attention since the late 19th century. One physical aspect that needs to be understood regarding urban climate problem is the urban heat island phenomenon. The steady economic growth and rapid urbanization has created increased concrete landscapes that can elevate the level of discomfort within the population due to this phenomenon. The problem is worsening in the Klang Valley area particularly, which is plagued by the extensive economic activities as well as the heat generated from factories, transport and air conditioners. This study examines the expansion of temporal urban growth by using Landsat images during different time periods according to the images' availability which were used under unsupervised classification. Meteorological data were also used to monitor historical temperatures. This finding indicates that the UHI intensity from the slope difference of urban and rural is 0.4º Celsius per decade. Datasets from remote sensing imageries found that the average rate of urbanization spread is 42.5 km2 per year. This study shows that the use of remote sensing is beneficial for multidisciplinary study. The mitigation of UHI can be proposed by considering steps such as planting trees and choosing ground paving material which are important measures in urban planning and decision making for future environment.